Let's Argue! Designing Satire in Digital Games. - Conway, Steven; Britton, Shaun (Design Issues)
This article presents an overview of the design of our digital game, Let's Argue. The project is an immanent critique of digital media, particularly the conventions of social and game applications as affording productive discourse between people, groups, and organizations. Focusing upon the concept of dialogue and its importance to society, we employ satire as a style, lampooning "social games" such as FarmVille and Candy Crush Saga. In aping, disrupting, and toying with these applications' representational and ludic facets, we provoke our users into considering how the medium, far from being neutral, shapes behavior and motivation.